Reproduction triggers adaptive increases in body size in female mole-rats. Issue 1880 (6th June 2018) - Thorley, Jack; Katlein, Nathan; Goddard, Katy; Zöttl, Markus; Clutton-Brock, Tim
Abstract : In social mole-rats, breeding females are larger and more elongated than non-breeding female helpers. This status-related morphological divergence is thought to arise from modifications of skeletal growth following the death or removal of the previous breeder and the transition of their successors from a non-breeding to a breeding role. However, it is not clear what changes in growth are involved, whether they are stimulated by the relaxation of reproductive suppression or by changes in breeding status, or whether they are associated with fecundity increases. Here, we show that, in captive Damaraland mole-rats ( Fukomys damarensis ), where breeding was experimentally controlled in age-matched siblings, individuals changed in size and shape through a lengthening of the lumbar vertebrae when they began breeding. This skeletal remodelling results from changes in breeding status because (i) females removed from a group setting and placed solitarily showed no increases in growth and (ii) females dispersing from natural groups that have not yet bred do not differ in size and shape from helpers in established groups. Growth patterns consequently resemble other social vertebrates where contrasts in size and shape follow the acquisition of the breeding role. Our results also suggest that the increases in female body size provide fecundity benefits. Similar forms of socially responsive growth might be more prevalent in vertebrates than is currently recognized, but the extent to which this is the case, and the implications for the structuring of mammalian dominance hierarchies, are as yet poorly understood.